2018
DOI: 10.1186/s13104-018-3774-y
|View full text |Cite
|
Sign up to set email alerts
|

Is nodding syndrome in northern Uganda linked to consumption of mycotoxin contaminated food grains?

Abstract: ObjectiveNodding syndrome (NS) is a type of epilepsy characterized by repeated head-nodding seizures that appear in previously healthy children between 3 and 18 years of age. In 2012, during a WHO International Meeting on NS in Kampala, Uganda, it was recommended that fungal contamination of foods should be investigated as a possible cause of the disease. We therefore aimed to assess whether consumption of fungal mycotoxins contributes to NS development.ResultsWe detected similar high levels of total aflatoxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…In Northern Uganda, the use of shea (Vitellaria nilotica) butter, simsim (Sesame indicum L.), and groundnut (Arachis hypogea L.) pastes as substitutes for refined cooking oil and vaseline with the belief that the latter are carcinogenic is known. Unfortunately, recent reports have pointed out that some of these food items are contaminated with mycotoxins, particularly aflatoxins which are potential carcinogens [19,235].…”
Section: Traditional Concept Of Cancer In Ugandamentioning
confidence: 99%
“…In Northern Uganda, the use of shea (Vitellaria nilotica) butter, simsim (Sesame indicum L.), and groundnut (Arachis hypogea L.) pastes as substitutes for refined cooking oil and vaseline with the belief that the latter are carcinogenic is known. Unfortunately, recent reports have pointed out that some of these food items are contaminated with mycotoxins, particularly aflatoxins which are potential carcinogens [19,235].…”
Section: Traditional Concept Of Cancer In Ugandamentioning
confidence: 99%
“…The methods for detection of AFs in agricultural foods have been reviewed in sufficient details by some Ugandan authors [13]. This also explains, in part, the fact that most AF investigations in Uganda following this review such as that of Muzoora et al [71], Echodu et al [69], Wacoo et al 476 [73] and Byakika et al [64] employed selective and highly sensitive methods. [85] Years cited represent the year the data were published with most data collected in over 2 months to 1 year.…”
Section: Methods Of Detection and Quantification Employed By Af Invesmentioning
confidence: 99%
“…In Uganda, AFB1 is the most studied [62] while AFM1 have received little attention [63]. Thus, most studies reported AFB1 levels or did not distinguish between the different types [64][65][66][67][68][69]. Others, such as the validation survey of Wacoo et al [70], Muzoora et al [71], Baluka et al [72] and Wacoo et al [73] differentiated the AFs.…”
Section: Etiologymentioning
confidence: 99%
“…In Uganda, AFB 1 is the most studied [56] while AFM 1 has received little attention [57]. us, most studies reported AFB 1 levels or did not distinguish between the different types [58][59][60][61][62][63]. Others, such as the validation survey of Wacoo et al [64], Muzoora et al [65], Baluka et al [66], and Wacoo et al [67], differentiated the AFs.…”
Section: Etiology Of Aflatoxins In Uganda and The Commodities Contamimentioning
confidence: 99%
“…Aflatoxigenic contamination in Uganda has been reported in maize (Zea mays L.) [59,62,63,69], sorghum (Sorghum bicolor L.), finger millet (Eleusine coracana) and their local products [58], peanuts (Arachis hypogaea L.) [57,65,66,70], cassava (Manihot esculenta) [71], rice (Oryza sativa) [72], sunflower (Helianthus annuus), sesame (Sesamum indicum L.) [63], animal feeds [73], and a bovine milk-based product [57]. AFs have also been detected in human sera [60,61,74].…”
Section: Commodities Contaminatedmentioning
confidence: 99%